The Musicalization of Fiction in Dorothy Richardson’s Pilgrimage and Virginia Woolf’s The Waves. - Abouabdelmajid, Mariyem; Anasse, Khadija (International Journal of Language and Literary Studies, 2025)
This article examines the relationship between the musicalization of fiction and the stream of consciousness techniques. It focuses on the intermediality, meaning, the superimposition of one art form on another as it is the case in Dorothy Richardson’s Pilgrimage (1919) and Virginia Woolf’s The Waves (1931). Both authors are considered modernists through their experimentation because they employ music as a theme and a structure. The qualitative method this study is based on fits this paper’s objectives since it analyzes the works of both writers who use musicalization of fiction. This article’s added value consists in a comparative study of both novels showing the ways the writers use thematization and mimesis of music creating a suitable prose for women. The article confirms that each author stands out by her own characteristics while sharing similarities and differences with the other. Indeed, Dorothy Richardson and Virginia Woolf use music to mirror the stream of consciousness of their characters. The authors’ interest in music comes from their musical knowledge and influence mostly by Beethoven and Wagner. However, while the musical flow serves as a connecting thread throughout Pilgrimage, The Waves reflects the rise and fall movements of the waves in a musical way.